ANALISIS EFEKTIVITAS BIAYA OBAT ANTIHIPERTENSI DOSIS TUNGGAL PADA PASIEN HIPERTENSI TANPA PENYAKIT PENYERTA: SYSTEMATIC LITERATURE REVIEW - Fahriati, Andriyani Rahmah; Fadilah, Adam Rizki; Rahmawati, Adelia; Denisa, Dila; Chasanah, Eneng Uswatun; Sahara, Khalipatun; Nurhakiki, Nurhakiki; Agustian, Rizki Zaidan; Fauziah, Shifa (PHRASE (Pharmaceutical Science) Journal, 2024)
Hypertension is a disease that occurs in various countries, especially Indonesia, where financing and health care are increasingly expensive. Based on data from the World Health Organization (WHO) in 2019, there were around 1,13 billionhypertension sufferers worldwide. Hypertension is a condition where a person experiences an increase in blood pressure above normal limits which can cause disease and even death. Pharmacoeconomic research is considered a suitable solution for policy makers in determining cost-effective clinical alternative treatments. The increasing costs of chronic diseases make access and quality of health services increasingly expensive, so solutions are needed to reduce health financing problems. The method used is cost effectiveness analysis (CEA). This systematic literature review aims to analyze single antihypertensive drugs in hypertensive patients without comorbidities using various related literature. Data were collected prospectively that met the inclusion and exclusion criteria. CEA analysis is calculated by looking at the ACER (Average Cost Effectiveness Ratio) value. From the overall results of the literature review, the most cost-effective antihypertensive drug is amlodipine, with the highest ACER range of 955.66 and the lowest 7,611. So it can be concluded that the most cost-effective antihypertensive therapy is amlodipine.